Digital Implementation of a Fault Emulator for Transient Study of Power Transformers Used in Grid Connection of Wind Farms - Mesbah, Mohsen; Moses, Paul; Islam, Syed; Masoum, Mohammad (The Institute of Electrical and Electronic Engineers (IEEE), 2013)
A real-time digital hardware simulation tool is developed to study the transient performance of three-phase power transformers used in grid connected wind farms. Using vector-based analysis for generating different voltage components, the fault simulator is capable of emulating a multitude of grid connection disturbances such as voltage sag, voltage swell, voltage unbalance, harmonics, dc-bias, and phase jump. This enables realistic real-time evaluation of power system faults and their impacts on critical components such as the interconnection transformers used in wind farms. In this paper, the proposed fault simulator has been employed to conduct an experimental study of the effects of balanced and unbalanced fault conditions on a three-phase three-leg power transformer. The transient current response of three-phase transformers subject to symmetrical/unsymmetrical faults is a complex issue due to the influences of multiple flux paths interacting within the core as well as ferromagnetic nonlinearities and core-structure asymmetry. So far, existing studies of this behavior have been restricted to computer modeling simulations with limited experimental work performed. The main contributions of this paper are to 1) present a new versatile fault simulator using a space vector modulation control approach to generate typical grid disturbances, and 2) apply the fault emulator to study the transient behavior of three-phase power transformers under various fault conditions common to wind farm interconnection transformers. The paper also discusses design, component selection, digital signal processing (DSP), and implementation aspects.